Sh.SEYITOVTÍŃ «XALQABAD» ROMANÍNDA GIDRONIMLERDIŃ QOLLANÍLÍWÍ - Mámbetova, G.J. (SCIENCE and SOCIETY, 2025)
The article analyzes the role of hydronyms used in Sh. Seyitov’s novel “Khalkobod” from a linguistic point of view. The article examines the semantics of hydronyms in the novel.
Keywords: onomastics; toponymy; hydronym; language of a work of art